Isoflavones as an alternative to menopausal hormone therapy - Bijak, Michał; Połać, Ireneusz; Borowiecka, Marta; Nowak, Paweł; Stetkiewicz, Tomasz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Isoflavones are members of flavonoids which belong to phytoestrogens, a group of non-steroid plant substances the chemical structure of which is similar to 17-β-estradiol. One of the richest sources of isoflavones is soybeans and legumes. The most important representatives of this class of compounds which have biological activity are daidzein and genistein. Isoflavones are able to bind to estrogen receptors (ER) however, their affinity to ER-β is higher than ER-α. Interaction isoflavones with ER lead to their activation. which causes cell response. The last epidemiological studies provide evidence that in Asia where soya is present in the traditional diet, women have less negative symptoms of menopause compared with the Western population. Clinical studies carried out in recent years have shown that soy protein or genistein supplementation reduces the number of hot flushes in post menopausal women. Similar results are shown for bone health. Genistein supplementation causes an increase in bone mineral density (BMD) and decrease in levels of bone resorption markers at a level comparable to hormone therapy. Isoflavones have also positive effects on the cardiovascular system. For all these reasons isoflavones are becoming an increasingly popular and safe alternative to hormone therapy for women with menopausal symptoms. This article describes the structure and metabolism of isoflavones as well as mechanism of action and results of clinical studies in postmenopausal women receiving isoflavones.